2016
DOI: 10.1073/pnas.1521238113
|View full text |Cite
|
Sign up to set email alerts
|

In vivo imaging identifies temporal signature of D1 and D2 medium spiny neurons in cocaine reward

Abstract: The reinforcing and rewarding properties of cocaine are attributed to its ability to increase dopaminergic transmission in nucleus accumbens (NAc). This action reinforces drug taking and seeking and leads to potent and long-lasting associations between the rewarding effects of the drug and the cues associated with its availability. The inability to extinguish these associations is a key factor contributing to relapse. Dopamine produces these effects by controlling the activity of two subpopulations of NAc medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

24
231
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 285 publications
(267 citation statements)
references
References 37 publications
24
231
1
Order By: Relevance
“…19) Moreover, chemogenetic inhibition of D1R-MSNs, but not D2R-MSNs, before the posttest blocks the expression of cocaine CPP. 20) Thus, although we expressed hM4Di in all vGAT-positive GABAergic neurons in the NAc, these findings suggest the involvement of subpopulations of MSNs in the expression of cocaine CPP. However, it should be noted that recent studies have shown that silencing NAc GABAergic parvalbumin (PV) interneurons blocks CPP induced by amphetamine, 21) while optogenetic activation of NAc PV interneurons produces aversion.…”
Section: Discussionmentioning
confidence: 65%
“…19) Moreover, chemogenetic inhibition of D1R-MSNs, but not D2R-MSNs, before the posttest blocks the expression of cocaine CPP. 20) Thus, although we expressed hM4Di in all vGAT-positive GABAergic neurons in the NAc, these findings suggest the involvement of subpopulations of MSNs in the expression of cocaine CPP. However, it should be noted that recent studies have shown that silencing NAc GABAergic parvalbumin (PV) interneurons blocks CPP induced by amphetamine, 21) while optogenetic activation of NAc PV interneurons produces aversion.…”
Section: Discussionmentioning
confidence: 65%
“…However, a crude summary seems permissible: dopamine in the accumbens is currently thought to serve at least 2 functions: (1) baseline dopamine and slow, that is, minute-to-minute, changes in accumbal dopamine (tonic DA release) seem to correlate with motivational vigor, reward rate, motivational vigor, and deprivation, whereas (2) fast, that is, second-to-second, changes in DA dopamine (phasic release) encode reward intensity/value as demonstrated by combinations of the most recent techniques [51,52,53,54]. …”
Section: Behavioral Consequences Of a Power Wielding-induced Increasementioning
confidence: 99%
“…No such correlation was found between the preference and the magnitude of the reduction of signals in D2-expressing neurons. Calipari et al (1) wisely interpret these results as evidence that high activation of D1-expressing neurons in the nucleus accumbens is largely responsible for coding the cocaine-context association. The study goes on to show that a history of cocaine exposure impairs the extinction of the preference, and it also enhances the magnitude of the preceding calcium signals in D1-expressing neurons.…”
mentioning
confidence: 98%
“…The study by Calipari et al in PNAS provides a glimpse into the in vivo pattern of neuronal activation in the mouse nucleus accumbens during the acquisition and expression of learned reward-context associations (1). The nucleus accumbens sits in the ventral part of the mouse striatum, and is required for reward-motivated learning.…”
mentioning
confidence: 99%
See 1 more Smart Citation